To find the remainder when the polynomial \( f(x) = x^4 - 3x^3 + 7x - 1 \) is divided by \( (x - 2) \), we can use the Remainder Theorem. According to the theorem, the remainder of a polynomial \( f(x) \) when divided by \( (x - c) \) is \( f(c) \).
In this case, we need to evaluate \( f(2) \):
\[ f(2) = (2)^4 - 3(2)^3 + 7(2) - 1 \]
Calculating each term:
- \( (2)^4 = 16 \)
- \( -3(2)^3 = -3(8) = -24 \)
- \( 7(2) = 14 \)
- The final term is \( -1 \)
Now substituting back into the equation:
\[ f(2) = 16 - 24 + 14 - 1 \]
Calculating step by step:
\[ f(2) = 16 - 24 = -8 \] \[ -8 + 14 = 6 \] \[ 6 - 1 = 5 \]
Thus, the remainder when \( f(x) \) is divided by \( (x - 2) \) is \( \boxed{5} \).